From diagnosis to therapy in Duchenne muscular dystrophy. (29th June 2020) - Babbs, Arran; Chatzopoulou, Maria; Edwards, Ben; Squire, Sarah E.; Wilkinson, Isabel V.L.; Wynne, Graham M.; Russell, Angela J.; Davies, Kay E.
Abstract : Genetic approaches for the diagnosis and treatment of inherited muscle diseases have advanced rapidly in recent years. Many of the advances have occurred in the treatment of Duchenne muscular dystrophy (DMD), a muscle wasting disease where affected boys are typically wheelchair bound by age 12 years and generally die in their twenties from respiratory failure or cardiomyopathy. Dystrophin is a 421 kD protein which links F-actin to the extracellular matrix via the dystrophin-associated protein complex (DAPC) at the muscle membrane. In the absence of dystrophin, the DAPC is lost, making the muscle membrane more susceptible to contraction-induced injury. The identification of the gene causing DMD in 1986 resulted in improved diagnosis of the disease and the identification of hotspots for mutation. There is currently no effective treatment. However, there are several promising genetic therapeutic approaches at the preclinical stage or in clinical trials including read-through of stop codons, exon skipping, delivery of dystrophin minigenes and the modulation of expression of the dystrophin related protein, utrophin. In spite of significant progress, the problem of targeting all muscles, including diaphragm and heart at sufficiently high levels, remains a challenge. Any therapy also needs to consider the immune response and some treatments are mutation specific and therefore limited to a subgroup of patients. This short review provides a summary of the current status of DMD therapy with a particular focus on those genetic strategies that have been taken to the clinic.